Effect of Liquid Nitrogen Fertilizers on the Increase of Cotton Yield Elements - Tukhtashev, F. E.; Davronov, Q. A. (European Journal of Life Safety and Stability (2660-9630), 2021)
The article presents the results of studying the effect of new liquid fertilizers on the growth, development of cotton and, most importantly, on the increase in the elements of cotton yield when it is treated with Уни-агроand Супер-КАСpreparations. In addition, the effect of liquid nitrogen fertilizers on an increase in the elements of cotton yield and fiber quality has been studied, and the optimal norms for their recommendation to production have been determined.